A retrospective observational study of intraductal breast papilloma and its coexisting lesions: A real‐world experience. (21st August 2020) - Li, Xiaona; Wang, Huan; Sun, Zhe; Fan, Chuifeng; Jin, Feng; Mao, Xiaoyun
Abstract: Background: Breast intraductal papilloma is a heterogeneous group. The aim of the study is to investigate the intraductal breast papilloma and its coexisting lesions retrospectively in real‐world practice. Methods: We retrospectively identified 4450 intraductal breast papilloma and its coexisting lesions. Results: About 18.36% of intraductal papilloma coexisted with malignant lesions of the breast, 37.33% coexisted with atypia hyperplasia (AH), 25.24% coexisted with benign lesions, and only 19.10% coexisted without concomitant lesions. In addition, 36.80% of intraductal breast papilloma had nipple discharge, 51.46% had a palpable breast mass, and 16.45% had both nipple discharge and a palpable breast mass. About 28.18% experienced discomfort or were asymptomatic. Furthermore, 98.99% had ultrasound abnormalities, and 53.06% had intraductal hypoechogenicity upon ultrasound. 31.89% had mammographic distortion, and 14.45% had microcalcification upon mammography. Intraductal breast papilloma with malignancy had significant correlations with clinical manifestations. Conclusion: Coexisting malignancy was also related to ultrasound abnormality (BIRADS 4C and 5), mammographic distortion, and microcalcification upon mammography but was not related to the intraductal hypoechoic upon ultrasound. Coexisting atypical hyperplasia correlated with nipple discharge but not palpable mass, mammographic distortion, or intraductal hypoechoic upon ultrasound. The coexisting AH was also related to abnormality upon ultrasound or microcalcification compared with the benign lesions. The intraductal papilloma coexists with malignancy or AH accounted for more than 50%, and the clinical information on papilloma and its coexisting lesions is nonspecific. We recommended surgical treatment for benign intraductal papillary lesions. Abstract : The current study provides insight into the real‐world pattern of the intraductal papillomas and their coexisting lesions in a population of Chinese women. We thought it is an important research on papilloma and breast cancer prevention.